Istifaadatu Ma'mal al-Lughoh fi Ta'lim Mahaarati al-Istima' fi al-Madrasah al-Tsaanawiyyah al-Hukuumiyyah Batu Jawa al-Syarqiyyah - Nasution, Marhamah; Rahmayanti, Indah (UIN Maulana Malik Ibrahim Malang, 2022)
The function of a good language laboratory is if the language laboratory is able to assist teachers in evaluating their students' learning effectively, not only partially, but significantly. This study aims to determine the use of the language laboratory in learning maharah istima' as well as the supporting and inhibiting factors in the use of the language laboratory at Senior High School of Batu. This study uses a qualitative approach with a descriptive type. Data collection techniques using observation, interviews and documentation. The results of the study indicate that the use of the language laboratory as a medium is one of the methods used by teachers to provide direct experience in the maharah istima' learning process. Therefore, the use of the language laboratory at Senior High School of Batu has functioned as it should. The supporting factors in the use of the language laboratory at Senior High School of Batu are resources, learning environment and teaching creativity. Meanwhile, the factors that cause the ineffective use of the language laboratory at Senior High School of Batu are the lack of training and skills for laboratory managers, the lack of competent laboratory technicians, and the lack of teacher knowledge about the use of laboratories.الكلمات الأساسية: استفادة، معمل اللغة، مهارة الاستماع.